Original Article Exploring the Efficacy of Telmisartan and Cilnidipine Combination Therapy in Hypertension: A Cross-sectional Analysis: Telmisartan-Cilnidipine Combo in Hypertension (Bombay Hospital Journal, 2026)
Introduction: Hypertension is a common non-communicable disease and is of major public health concern accounting for19% of all deaths globally. The lack of awareness about hypertension is a major contributory factor for the delayed diagnosisof asymptomatic cases, thus being labeled as a “silent killer disease.” Effective control of blood pressure is a must andfor achieving it, a long-acting antihypertensive agent is required. Telmisartan is one of the angiotensin II receptor blockerswhereas cilnidipine is a novel calcium antagonist. Cilnidipine has shown prolonged and desirable antihypertensive effects. Thepresent questionnaire-based study conducted on various clinicians across different parts of the country analyses the patternof patients with hypertension and other comorbidities in their clinical practice along with the trend in the prescription ofantihypertensives either mono and/or combination therapy. Materials and Methods: The present study is a questionnairebasedcross-sectional study consisting of 25 validated structured questions. The study was approved by the InstitutionalEthical Committee. All the completed forms were included in the study whereas incomplete form was excluded from thestudy. Observation and Results: The survey reflects that 87% of the patients have diabetes mellitus as one of the mostcommon comorbid conditions associated with hypertension. About 86.5% of the clinicians (86.5%) are of the opinion thatmore than 30% of the patients required combination therapy of telmisartan and cilnidipine with the addition of diuretics inuncontrolled hypertension. The combination also offers many other benefits such as its anti-atherosclerotic properties and endorganprotection. Conclusion: The study highlights that combination therapy is very effective in treating hypertension even ifassociated with other comorbid conditions such as diabetes and chronic kidney disease.
Keywords: Cilnidipine, Combination therapy, Diuretics, Hypertension, Telmisartan